Bridging the Digital Divide: Policy Solutions for Improving Digital Health Literacy and Healthcare Accessibility - Maulia, Jihan Tasyabitah Tri (Yayasan Sinergi Kawula Muda, 2023)
Digital health literacy (DHL) is a fundamental determinant of individuals’ ability to navigate, assess, and utilize online health information effectively. This study examines the systemic factors influencing DHL outcomes, the role of public health institutions in mitigating literacy disparities, and the implications for healthcare accessibility. A systematic review methodology was employed, analyzing literature from databases such as PubMed, Scopus, and Google Scholar. The findings highlight that healthcare policies, education systems, and cultural factors shape individuals’ digital health competencies. While digital health interventions improve access to health information, barriers such as misinformation, digital divides, and disparities in digital competencies persist. Public health institutions play a critical role in addressing these challenges through structured education programs, policy advocacy, and targeted community engagement initiatives. The study underscores the necessity of integrating digital health literacy training into educational curricula, professional development for healthcare providers, and public health campaigns to enhance equitable healthcare access. Future research should focus on evaluating DHL interventions, standardizing assessment frameworks, and exploring strategies to combat misinformation in digital health contexts. Improving digital health literacy is essential for empowering individuals, enhancing patient engagement, and fostering more inclusive digital healthcare environments.